2022
DOI: 10.3390/polym14194141
|View full text |Cite
|
Sign up to set email alerts
|

Nanogels as Potential Delivery Vehicles in Improving the Therapeutic Efficacy of Phytopharmaceuticals

Abstract: Nanogel is a promising drug delivery approach to improve the pharmacokinetics and pharmacodynamic prospect of phytopharmaceuticals. In the present review, phytopharmaceuticals with astonishing therapeutic utilities are being explored. However, their in vivo delivery is challenging, owing to poor biopharmaceutical attributes that impact their drug release profile, skin penetration, and the reach of optimal therapeutic concentrations to the target site. Nanogel and its advanced version in the form of nanoemulgel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…It was concluded that the positive charge of chitin strongly interacts with the stratum corneum to loosen the keratin, achieving drug accumulation into the deeper skin layers [ 122 ]. Moreover, capsaicin nanoemulgels (advanced form of nanogels) compared to conventional capsaicin-loaded gels revealed better skin permeation, which is attributed to the tunable size and shape of the nanogel particles [ 123 , 124 ]. An in vivo study of cutaneous application of paromomycin entrapped in stimuli-sensitive block copolymer nanogel dispersions for the management of leishmaniasis demonstrated that the nanogels have better antileishmanial ability than pure drug.…”
Section: Applications Of Nanogels As Drug Delivery Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that the positive charge of chitin strongly interacts with the stratum corneum to loosen the keratin, achieving drug accumulation into the deeper skin layers [ 122 ]. Moreover, capsaicin nanoemulgels (advanced form of nanogels) compared to conventional capsaicin-loaded gels revealed better skin permeation, which is attributed to the tunable size and shape of the nanogel particles [ 123 , 124 ]. An in vivo study of cutaneous application of paromomycin entrapped in stimuli-sensitive block copolymer nanogel dispersions for the management of leishmaniasis demonstrated that the nanogels have better antileishmanial ability than pure drug.…”
Section: Applications Of Nanogels As Drug Delivery Carriersmentioning
confidence: 99%
“…In addition, the physicochemical properties of polymers used for the development of the nanogels can govern the mechanical strength, thixotropic characteristics, and functionality; the features of the polymer are dictated by the monomer chemical nature, molecular weight, methodology, and macromolecular structure [ 123 ]. Carbopol 940 is a potent gelling agent, and it has been widely used for the formation of hydrogels, conventional gels and nanogels.…”
Section: Applications Of Nanogels As Drug Delivery Carriersmentioning
confidence: 99%
“…Os gelificantes são introduzidos na formulação para transformar o estado líquido da nanoemulsão e resolver os problemas de baixa viscosidade e espalhabilidade limitada, facilitando a aplicação, a bioadesão, e administração percutânea de ativos. São exemplos práticos a carboximetilcelulose de sódio, a hidroxipropilmetilcelulose, carbômeros e polissacarídeos derivados de plantas (FERNANDO et al,2022;OJHA et al, 2022;SULTANA et al, 2022;TAHA et al, 2022;DONTHI et al, 2023;LAL et al, 2023). A Figura 1 representa etapas de produção dos nanoemulgéis.…”
Section: Métodos De Preparo Dos Nanoemulgéisunclassified
“…Outro fato interessante, acerca das nanoemulsões, é que as gotículas da fase dispersam possuem carga elétrica devido a presença dos vários agentes emulsificantes e estabilizantes. A magnitude da repulsão entre as gotículas aumenta com o potencial zeta, essa propriedade aumenta a estabilidade da formulação, ou seja, as gotículas não conseguem se agregar devido elevado potencial zeta, assim, a presença de tensoativos aniônicos ou catiônicos são cruciais para a estabilidade da nanoelumsão (FERNANDO et al,2022;OJHA et al, 2022;SULTANA et al, 2022;TAHA et al, 2022;DONTHI et al, 2023;LAL et al, 2023).…”
Section: Caracterização Dos Nanoemulgéisunclassified
“…In these cases, a nanoemulgel can be formed by adding polymers, such as carbomers, poloxamer 407 and xanthan gum, to the nanoemulsion’s aqueous phase. At specific concentrations, these polymers will transform the aqueous phase into an in situ gel, which will be formed when the formulation is subjected to specific conditions, such as pH, temperature and the presence of mono or divalent cations, respectively [ 75 , 76 , 77 , 78 ].…”
Section: Introductionmentioning
confidence: 99%